Kinerja Lingkungan, Biaya Lingkungan dan Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderating - Putri, Miranti Kencana; Susanti, Efi (E-Jurnal Akuntansi; Vol 33 No 2 (2023)DO - 10.24843/EJA.2023.v33.i02.p18, 2023)
The research aims to determine and analyze the effect of environmental performance and environmental costs on company value with profitability as a moderating variable in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. This research is a quantitative study, the population in the study is mining sector companies listed on the IDX by using purposive sampling techniques. The samples used were 10 companies with a total of 40 observations. The data analysis technique used is moderation regression analysis. The results of environmental performance research have no effect on firm value and environmental costs have no effect on firm value. Moderation analysis of the profitability variable is able to moderate the relationship between environmental performance and firm value, and the profitability variable cannot moderate the relationship between environmental costs and firm value. Keywords: Environmental Performance; Environmental Costs; Profitability; Firm Value